Analysis of physiological response to training and competition among Finnish endurance athletes - Rusko, H. (Athletic Performance Review, 1986)
Terminal lactates were taken on Finnish cross-country skiers at the end of championship events (males 15 km and females 5 km). The following were found for the males: - High finish lactates were found in athletes who were fast at the half-way mark and then slowed. - Lower lactates were recorded in athletes who performed more evenly. - There was no difference in performance between the groups even though there was considerable variation in lactate measures between them. The following were found for the females: - Those with high finish lactates started fast, slowed and finished in poorer placings than the low lactate group. - The low lactate group finished with better placings. Implications: There is little value in post-race lactates for they do not relate to absolute race placings. They do seem to be slightly related to the fast out -- slow home, type of race pacing. Even pacing of effort is crucial for cross-country skiing.